1964
DOI: 10.1126/science.143.3611.1177
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Microsomal RNA into Five Bands during Agar Electrophoresis

Abstract: Microsomal RNA from rabbit livers and lymph nodes separate into five major bands during agar-gel electrophoresis. The electrophoretic method may be used either as an analytical or preparative tool. The 33S and 19S peaks of microsomal RNA from sucrose-gradient zone centrifugation divide into two bands each during simple agar electrophoresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1965
1965
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…They found that the mobility was independent of size for DNA molecules larger than ∼400 base pairs (bp) 5, and varied with ionic strength 3, 5 and the identity and valence of the cation in the background electrolyte 2, 3. At about the same time, inspired by the separation of proteins in synthetic gel matrices 6–10, other investigators began to use similar matrices to separate RNA 11–19 and DNA molecules 15, 20–24 by molecular mass. The separation matrices included agar 11, 18, 20, 21, agarose 22, 23, polyacrylamide 13, 14, 19, 24–28 and composite agarose‐acrylamide 16, 17 gels.…”
Section: Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the mobility was independent of size for DNA molecules larger than ∼400 base pairs (bp) 5, and varied with ionic strength 3, 5 and the identity and valence of the cation in the background electrolyte 2, 3. At about the same time, inspired by the separation of proteins in synthetic gel matrices 6–10, other investigators began to use similar matrices to separate RNA 11–19 and DNA molecules 15, 20–24 by molecular mass. The separation matrices included agar 11, 18, 20, 21, agarose 22, 23, polyacrylamide 13, 14, 19, 24–28 and composite agarose‐acrylamide 16, 17 gels.…”
Section: Historical Overviewmentioning
confidence: 99%
“…At about the same time, inspired by the separation of proteins in synthetic gel matrices 6–10, other investigators began to use similar matrices to separate RNA 11–19 and DNA molecules 15, 20–24 by molecular mass. The separation matrices included agar 11, 18, 20, 21, agarose 22, 23, polyacrylamide 13, 14, 19, 24–28 and composite agarose‐acrylamide 16, 17 gels. As electrophoretic methods were improved by the purification of agarose 29–31 and the use of slab gels instead of tube gels 25, 32, and as the discovery of restriction enzymes allowed the preparation of monodisperse DNA fragments of known size 33, 34, it became apparent that the separation of DNA fragments by molecular mass depended on the gel matrix in which the separation was carried out 33, 35.…”
Section: Historical Overviewmentioning
confidence: 99%
“…We have used the technique of agar-gel electrophoresis that was further developed as an analytical method for RNA fractionation by Tsanev & Staynov (1964). This method was shown to have a better resolving power than sucrose-densitygradient centrifugation (Bachvaroff & McMaster, 1964;Tsanev, 1965a,b). It is possible to study by radioautography the incorporation of labelled precursors into different electrophoretic fractions by using dry agar electrophoretograms.…”
mentioning
confidence: 99%
“…For fractionation of RNA species, a modification of the electrophoretic method on agarose-polyacrylamide gels described by Peacock and Dingman (1968) was used. Electrophoretic separation of RNA was first described with agar as gel substance (Bachvaroff and McMaster 1964), and there has been many indications that gel techniques are capable of higher resolution than the more commonly used techniques of zone sedimentation and column chromatography. Agar gel electrophoresis seems to be most valuable in fractionation of high molecular weight RNA.…”
Section: Discussionmentioning
confidence: 99%